(untitled) (Journal on Geoinformatics, Nepal, 2016)
Economic growth rate of any country largely depends on the development of mineral sector. Then, the level of technology employed for meeting the extraction conditions must meet environmental norms. Exploration of mineral resources in India and mining is a ready application for technologies for ensuring productivity and efficiency. Use of Geographical Information System (GIS) in mineral resources management is of great help, where each stakeholder can access, use and exchange spatial and nonspatial data for social, economic and environmental activities. With development of communication and information technology, integration of heterogeneous repository of data from the different data sources can be achieved by using Spatial Data Infrastructure (SDI). At the present scenario, the dynamic updating of data, data analysis, data visualisation and data uploading are lacking in most of the information system in GIS environment. For real time integrated mineral resources information monitoring, it is essential to integrate information system with geospatial database. Visualisation of integrated mineral resources information is possible on the desktop environment with the help of GIS. But it is not sufficient for updating the data in dynamic environment. It may be possible to perform dynamic tasks like update, analysis and visualisation of mineral resources information through the mobile devices with the modern high end mobile communication infrastructure. It makes it possible and very useful to take the decision at anytime from anywhere in the world. The data repositories can also be timely updated with the help of common mobile devices from any location, of course with security measure in place. In the present work, a three tier secure framework has been proposed for the mobile based SDI Model for the better management of mineral resources information infrastructure with the use of mobile devices by the integration of geospatial database. The interaction between the various services in the proposed Model has been modeled by using Unified Modeling Language (UML) use case and activity diagrams.